2020
DOI: 10.1126/sciadv.abb8783
|View full text |Cite
|
Sign up to set email alerts
|

RELATe enables genome-scale engineering in fungal genomics

Abstract: CRISPR-Cas9–based screening with single-guide RNA (sgRNA) libraries has emerged as a revolutionary tool for comprehensive analysis of genetic elements. However, genome-scale sgRNA libraries are currently available only in a few model organisms. The traditional approach is to synthesize thousands to tens of thousands of sgRNAs, which is laborious and expensive. We have developed a simple method, RELATe (restriction/ligation coupled with Agrobacterium-mediated transformation), to generate sgRNA libraries from 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The CNAG_05141 Δ mutant had minor sensitivity to EMS compared to the wild-type control, and was not sensitive to UV damage. Based on AlphaFold and FoldSeek analysis, this protein contained a predicted EamA-like transporter domain [ 73 ] and had structural homology to the Nipal2 and Nipa1 transporter proteins. Potentially, loss of this transporter may lead to a higher intracellular concentration of EMS resulting in increased cell death.…”
Section: Resultsmentioning
confidence: 99%
“…The CNAG_05141 Δ mutant had minor sensitivity to EMS compared to the wild-type control, and was not sensitive to UV damage. Based on AlphaFold and FoldSeek analysis, this protein contained a predicted EamA-like transporter domain [ 73 ] and had structural homology to the Nipal2 and Nipa1 transporter proteins. Potentially, loss of this transporter may lead to a higher intracellular concentration of EMS resulting in increased cell death.…”
Section: Resultsmentioning
confidence: 99%
“…albicans ( S1 Table ). As a previous independent study named CNAG_02402 WDR1 [ 25 ], we denoted it as WDR1 instead of WDR7 .…”
Section: Resultsmentioning
confidence: 99%
“…At present, large-scale and high-throughput genetic screens based on CRISPR-Cas9 have been achieved in mammalian cells through the transformation of sgRNA libraries which is commercially available [ 32 , 33 ]. In the studies of pathogenic fungi, Li et al, 2010, exploited a similar method called restriction/ligation coupled with Agrobacterium-mediated transformation (RELATe), which generated sgRNA libraries from Cryptococcus neoformans genomic DNA and covered 98% of the protein-coding genes [ 34 ]. In C. albicans , the genetic screen based on CRISPR-Cas9 and sgRNA libraries has not been reported, which indicated that the construction of sgRNA libraries, high-efficient transformation, recovery, and sequencing of sgRNA should be further explored.…”
Section: Methods Used In the Mutant Library Construction In ...mentioning
confidence: 99%